Testimony a novel - Shreve, Anita (New York : Little, Brown, 2008)
At a New England boarding school, a sex scandal is about to break. Even more shocking than the sexual acts themselves is the fact that they were caught on videotape. A Pandora's box of revelations, the tape triggers a chorus of voices--those of the men, women, teenagers, and parents involved in the scandal--that details the ways in which lives can be derailed or destroyed in one foolish moment
Keywords: Boarding schools -- Fiction; Teenage girls -- Fiction; Scandals -- Fiction; Suspense fiction